2017
DOI: 10.1111/jon.12453
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Multislice–Based 5‐Minute Lumbar Spine MRI Protocol: Initial Experience in a Clinical Setting

Abstract: A 5-minute SMS-based MRI protocol for lumbar spine imaging is feasible and can be achieved without significant impact in the overall diagnostic quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The resulting acquisition times of 01:23–02:39 min per sequence and 07:59 min for the entire imaging protocol render 0.55 T low-field MRI of the lumbar spine competitive to current imaging protocols at higher field strengths. Fore reference, Sartorreti et al reported a total scan time of 11:28 min when using parallel imaging at 1.5 T in 2019 [25] and Longo et al achieved a protocol time of 5:28 min by the help of simultaneous multislice imaging at 3 T in 2022 [26] . The reduction in acquisition time trough deep learning reconstruction in our is comparable to other recently published investigations, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting acquisition times of 01:23–02:39 min per sequence and 07:59 min for the entire imaging protocol render 0.55 T low-field MRI of the lumbar spine competitive to current imaging protocols at higher field strengths. Fore reference, Sartorreti et al reported a total scan time of 11:28 min when using parallel imaging at 1.5 T in 2019 [25] and Longo et al achieved a protocol time of 5:28 min by the help of simultaneous multislice imaging at 3 T in 2022 [26] . The reduction in acquisition time trough deep learning reconstruction in our is comparable to other recently published investigations, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…18 Accelerated MRI techniques such as parallel imaging and compressed sensing have been developed and applied in recent years, leading to a marked reduction in acquisition times. [19][20][21][22][23] DL techniques have gained significant attention and importance in various fields, especially neuroimaging. 24 As a subfield of artificial intelligence (AI), DL has revolutionized the way clinical imaging is performed, offering innovative solutions for disease diagnosis, detection, and tumor segmentation.…”
Section: Introductionmentioning
confidence: 99%
“…18 Accelerated MRI techniques such as parallel imaging and compressed sensing have been developed and applied in recent years, leading to a marked reduction in acquisition times. 1923…”
Section: Introductionmentioning
confidence: 99%
“…In the past three decades, various acceleration techniques have been introduced in MRI. [4][5][6][7] Parallel imaging harnesses multiple receiver coils to simultaneously collect the MRI data. 8 Partial Fourier capitalizes on inherent data redundancy due to Hermitian symmetry, collecting only a fraction of the k-space.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Nowadays, by integrating these acceleration techniques, routine spine MRI has already trimmed its total acquisition time to approximately 5 minutes without compromising diagnostic performance. 5 However, the footsteps towards faster skeletal imaging should not be ended. Despite the achievement, spine MRI still holds much longer acquisition time compared to CT.…”
Section: Introductionmentioning
confidence: 99%